2021
DOI: 10.1177/19714009211026925
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following aneurysmal coil embolization with intentionally shortened low-profile visible intraluminal support stent deployment

Abstract: Purpose Among all stents available for neuroendovascular therapy, the low-profile visible intraluminal support stent bears the highest metal coverage ratio. We deployed a low-profile visible intraluminal support stent with a delivery wire or/and microcatheter system push action to shorten the low-profile visible intraluminal support stent and thus achieve a flow diversion effect. We report our single-institution experience with the use of low-profile visible intraluminal support stents for intentionally shorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…This is an unexpected finding given the abundance of clinical and simulation studies that have suggested that there is a possible relationship between the aneurysm obliteration rate and a decreased porosity/increased pore density at the aneurysm neck. 12,17,[22][23][24] One reason for the lack of such an association in our study may be that bifurcation aneurysms do not respond to flow diversion as well as sidewall aneurysms. All of the aneurysms in our study were bifurcation aneurysms.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…This is an unexpected finding given the abundance of clinical and simulation studies that have suggested that there is a possible relationship between the aneurysm obliteration rate and a decreased porosity/increased pore density at the aneurysm neck. 12,17,[22][23][24] One reason for the lack of such an association in our study may be that bifurcation aneurysms do not respond to flow diversion as well as sidewall aneurysms. All of the aneurysms in our study were bifurcation aneurysms.…”
Section: Discussionmentioning
confidence: 59%
“…The SBT has been described using various terms in the literature, such as the "shelf technique," "barrel technique," "stent bulging," "compressed stent," "intentional stent herniation," "intentional shortening," "compaction," or "wrapped-candy" techniques. 8,11,12,[15][16][17][18][19] Although some authors prefer to use the term "compression/compaction" for all types of aneurysms, on the basis of our review of the relevant literature, we think that the terms "compression," "compaction," "shortening," and "wrapped-candy" should be reserved for sidewall aneurysms, whereas "shelf," "herniation," or "bulging" should be used for bifurcation aneurysms. Technically, the maneuvers performed to achieve a compacted stent are similar in both scenarios; however, the intent (the ability to preserve a side branch versus the desire to achieve a better flow diversion) and the immediate angiographic results (bulged stent versus shortened stent) are different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation